1995
DOI: 10.1007/bf02246209
|View full text |Cite
|
Sign up to set email alerts
|

Nicergoline in senile dementia of alzheimer type and multi-infarct dementia: a double-blind, placebo-controlled, clinical and EEG/ERP mapping study

Abstract: In a double-blind, placebo-controlled study on the therapeutic efficacy and central effects of nicergoline, an ergot alkaloid with metabolic, antithrombotic and vasoactive action, 112 patients with mild to moderate dementia, diagnosed according to DSM III-R criteria (MMS 13-25), living in pensioners' homes, were included. Fifty-six were subdiagnosed as senile dementia of the Alzheimer type (SDAT), 56 as multiinfarct dementia (MID), based on computed tomography and Hachinski scores (< or = 49 SDAT, > or = 7 MID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(76 citation statements)
references
References 37 publications
3
70
0
3
Order By: Relevance
“…However, it is very difficult to draw any firm conclusions in the absence of randomized placebo-controlled studies of large populations. In a double-blind, placebo-controlled study [21], 112 patients were treated with nicergoline, a thrombolytic, vasoactive ergot alkaloid. Nicergoline improved vigilance and information processing in the neuropsychological assessment of patients with degenerative and vascular dementia.…”
Section: Curative Treatmentmentioning
confidence: 99%
“…However, it is very difficult to draw any firm conclusions in the absence of randomized placebo-controlled studies of large populations. In a double-blind, placebo-controlled study [21], 112 patients were treated with nicergoline, a thrombolytic, vasoactive ergot alkaloid. Nicergoline improved vigilance and information processing in the neuropsychological assessment of patients with degenerative and vascular dementia.…”
Section: Curative Treatmentmentioning
confidence: 99%
“…In mildly demented patients, the centroparietal P300 amplitude increased after one treatment intravenously with 0.2 g amantadine sulfate [11] and in mildly to moderately demented patients with probable dementia of Alzheimer's type and with multi-infarct dementia, P300 latency was shortened after 8 weeks' treatment with 2 ! 30 mg nicergoline [12]. Moreover, the shortening of P300 latency and the improvement of the cognitive dysfunction were significantly correlated [13].…”
Section: Introductionmentioning
confidence: 99%
“…The best-studied ergot rye derivative is the ergoloid mesylate Hydergine ® ; a review of 151 studies showed that it induces a modest improvement in cognition, daily activities and behavior [30]. Nicergoline (Sermion ® ), as observed in a small number of studies, improves cognition, vigilance and the EEG trace, both in AD and VaD [31][32][33]. The combination of almitrine and raubasine (Duxil ® ), reviewed by Allain and Bentué-Ferrer [34], improves many cognitive parameters as well as the neurosensory symptoms of ischemia/hypoxia (e.g.…”
Section: Medicines Vasodilators Oxygenators Ergot Rye Derivativesmentioning
confidence: 99%